KONFLIK PEMANFAATAN AREA PANTAI DI DESA PERMAI KECAMATAN RANGSA BARAT KABUPATEN MERANTI - Muhammad Yusuf Aad Eka Putra; Syamsul Bahri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
High abrasion in the beach area to conflict in Desa Permai Meranti District Subdistrict stimuli. Conflict utilization of coastal areas in the village on Permai between traders with the mangrove group caused because the disagreements between the two sides. Where traders who sell there refused planted mangrove shore to pieces because he planted mangrove feared would cover the coast, thereby reducing the interest of visitors to visit the beach to pieces, according to traders, at the beach shredding already be built solver wave to hold abarasi making the mangrove planting is not considered effective , the refusal to traders not accepted mangrove group which is also an activity proposed by the government in order to overcome the abrasion in the region. giving rise to a conflict between the two communities studied. The conflict this time located in Desa Permai Meranti District Subdistrict stimuli that area there are informants who know the information even directly involved in the conflict in accordance with the subject under study. Data retrieval research conducted by interview, observation and documentation. Interviews were conducted is a structured interview where researchers first prepare interview guidelines. This time researchers will identify the causes of conflict and the role of government in the conflict in Desa Permai resolusi Rangsang District of West County MerantiKeywords: Conflict, Conflict Resolution, Coastal Area.